Pendidikan Islam Berbasis Rekonstruksi di Era Globalisasi - Anisa Al Iffah; M. Nabil At-Tammy; Wini Fatmawati; Herlini Puspika Sari (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background of this research is to provide a comprehensive understanding of Islamic education in the era of globalization. The focus is on the concept of Islamic education based on reconstruction as a response to social changes and global influences. And referring to the views of experts, this research uses qualitative literature study methods to analyze the concept of Islamic education and the flow of reconstructionism. The research results highlight the importance of facing the negative impact of globalization on Islamic education and emphasize the need to protect Islamic teachings in the face of technological advances, while also emphasizing the importance of creating a generation that is not only intellectually intelligent, but also has moral integrity and readiness to face global change. By involving the role of educators, curriculum and learning methods, reconstruction-based Islamic education is expected to be able to create a strong foundation for overcoming challenges and exploiting opportunities in the context of globalization.